Urban integration of forced migrants: lessons from Canada and Ukraine - Venhryn, Daria (Visnyk of V. N. Karazin Kharkiv National University. Series Geology. Geography. Ecology, 2024)
Statement of the problem. Active hostilities began in Ukraine, leading to the imposition of a state of war in the country on 24 February 2022. This has resulted in a mass displacement, with citizens leaving their homes in search of safety and protection. Currently, 3.6 million people have left Ukraine, while 6.5 million people are internally displaced. These unprecedented migration flows have created immense challenges for both the displaced populations and the host communities that strive to accommodate them. In the face of extraordinary challenges, Canada was one of the first countries to come to Ukraine’s aid. The Canadian government facilitated the visa process for Ukrainians, allowing them to migrate to Canada. The aim of the work is to analyze and evaluate the impact of migrants on urban development, focusing on the cases of Ukraine and Canada. Methods. In the course of the research and preparation of the article, the author used methods of analysis and synthesis, comparative-geographical and comparative-historical approaches, as well as the method of generalization. Results. This article delves into two critical aspects of Ukrainian migration during the ongoing war: internal displacement within Ukraine and international migration to Canada. We analyze the settlement patterns of migrants and the pressure they exert on cities. The geographical distribution is diverse. IDPs settle both in cities near the frontlines and in western regions in Ukraine. Despite all the risks, Kyiv the capital city of Ukraine, remains highly attractive. When relocating to Canada, migrants are guided by two factors: either having acquaintances, relatives, or friends already living there, or simply choosing a well-known large city. As research indicates, various sectors of urban infrastructure and services face challenges and opportunities under the influence of migration. Canada demonstrates effective integration through its well-developed laws, inclusive policies, and support systems that protect migrants’ rights, fight discrimination, and provide essential services. The Ukrainian diaspora plays a significant role in this process by helping newcomers adapt. Ukraine’s experience with internal migration caused by armed conflict shows the country’s challenges in managing large-scale resettlement. The lack of housing, jobs, and social services pushed local authorities to respond quickly to the situation and learn from the practices of other countries. Our analysis underscores the need for strategic planning and investment to ensure sustainable urban development in the face of large-scale migration. Understanding the implications of these movements is essential for building resilient communities and addressing the complex challenges posed by displacement. The novelty. For the first time, the readiness of Canadian and Ukrainian cities to accommodate migrants was compared. Furthermore, the study analyzed how various sectors of urban infrastructure and services adapt to challenges and take advantage of opportunities created by migration.